1995
DOI: 10.1111/j.1476-5381.1995.tb13282.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of RS 25259‐197, a potent and selective antagonist, with 5‐HT3 receptors, in vitro

Abstract: 1 A series of isoquinolines have been identified as 5-HT3 receptor antagonists. One of these, RS 25259-197 [(3aS)-2-[(S)-l-azabicyclo[2.2.2]oct-3-yl]-2,3,3a,4,5,6-hexahydro-l-oxo-lH-benzo [de]isoquinoline-hydrochloride], has two chiral centres. The remaining three enantiomers are denoted as RS 25259-198 (R,R), RS25233-197 (S,R) and RS25233-198 (R,S). 2 At 5-HT3 receptors mediating contraction of guinea-pig isolated ileum, RS 25259-197 antagonized contractile responses to 5-HT in an unsurmountable fashion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 45 publications
4
120
1
4
Order By: Relevance
“…*Statistically significant from vehicle control (P<0.05). (Wong et al, 1994) whereas the reported pKi values for ondansetron and granisetron in rat tissues range from 8.3-9.0 (for ondansetron) and from 9.2-9.8 (for granisetron) (Kilpatrick et al, 1990 Oral administration of drugs to cancer patients undergoing chemotherapy is problematic owing to the high incidence of emesis in these patients. Thus, availability of a 5-HT3 receptor antagonist in the form of a transdermal formulation would greatly facilitate the management of emesis in these patients.…”
Section: Haemodynamic Effects In Anaesthetized Dogsmentioning
confidence: 99%
“…*Statistically significant from vehicle control (P<0.05). (Wong et al, 1994) whereas the reported pKi values for ondansetron and granisetron in rat tissues range from 8.3-9.0 (for ondansetron) and from 9.2-9.8 (for granisetron) (Kilpatrick et al, 1990 Oral administration of drugs to cancer patients undergoing chemotherapy is problematic owing to the high incidence of emesis in these patients. Thus, availability of a 5-HT3 receptor antagonist in the form of a transdermal formulation would greatly facilitate the management of emesis in these patients.…”
Section: Haemodynamic Effects In Anaesthetized Dogsmentioning
confidence: 99%
“…[13][14][15][16][17] Palonosetron may also have other advantages for perioperative care. For example, a recent study reported by Cho et al 34 found that palonosetron 0.075 mg iv administered before induction of anesthesia reduced injection pain associated with rocuronium administration; the NNT was 2.94.…”
Section: Discussionmentioning
confidence: 99%
“…Méthodes Nous avons effectué une recherche systématique dans les bases de données MEDLINE Ò , EMBASE TM , le Registre central Cochrane des essais cliniques contrô lés et Web of Science Ò pour identifier les essais randomisés contrô lés qui ont abordé la comparaison de l'efficacité antiémétique dans les 24 premières heures suivant une chirurgie, du palonosétron et de l'ondansétron administrés à titre prophylactique. Les principaux critères d'évaluation étaient le pourcentage de participants éprouvant des nausées postopératoires (NPO), des vomissements postopératoires (VPO) ou les deux, dans la période précoce (0-6 heures) ou tardive (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Postoperative nausea and vomiting (PONV), the big ''little problem'', 1 is the most common postoperative medical problem. From the perspective of both patients and healthcare providers, prophylaxis of PONV is equally as important as postoperative analgesia.…”
Section: Résuméunclassified
See 1 more Smart Citation
“…30 Starting from our experience with palonosetron plus dexamethasone in multiple-day CT, 29 the present study evaluated the efficacy, in terms of complete response (no emesis, no rescue therapy), of a single dose of palonosetron administered on the first day of a conditioning regimen together with dexamethasone administered throughout the entire period of conditioning in hematological patients receiving HD-CT and auto-SCT.…”
Section: Introductionmentioning
confidence: 99%